An improved preloaded Curvic coupling model for rotordynamic analyses. (3rd February 2023) - Kim, Baik Jin; Oh, Joseph; Palazzolo, Alan
Highlights: Test validation of superior accuracy with novel Curvic coupling model. Parametric study for tooth contact, number, pressure angle, half pitch number. Combining GW surface asperity contact and flexible disc/tooth models. Industrial application demonstrates importance of the modelling improvements. Rigid coupling tooth and disc assumptions lead to significant errors. Uniform continuous beam model introduces large errors relative to test. Abstract: Curvic couplings are commonly utilized in aircraft engines and large gas turbines for high load capacity, precision centering of stacked components in rotating assemblies. The couplings have non-axisymmetric, complex curved mating contact surfaces, which transmit torque, moment and force. Coupling contact surface roughness, and tooth and ring deformations introduce local lateral flexibilities, compared with a continuous beam model, and consequently affect rotordynamic vibration predictions. A novel approach of modeling the Curvic coupling is proposed which combines a GW contact model with a 3D solid element model of flexible teeth and coupling rings. This improves on similar approaches that assume rigid teeth and rings or omits a surface roughness – asperity model. Comparisons of the various models with experimental measurements of free-free natural frequencies of an axially preloaded shaft, demonstrate a marked improvement in accuracy with the proposed approach. A parametric study is performed which varies tooth contact pattern, tooth number, pressure angle, half pitch number, and tooth rigidity to evaluate their effects on vibration and stress. The proposed approach is also applied to an industrial rotor to illustrate the effect of the new Curvic coupling model on critical speeds. The higher fidelity flexible tooth model presented shows a significant change in critical speed relative to the rigid tooth model from the literature. Graphical abstract: Image, graphical abstract